Analysis of The Relationship of Rework and Inventory to Waste in The Ciputra Hospital Surabaya Project - Ferdiandika, Ahmad Fadhil; Nuciferani, Felicia Tria; Choiriyah, Siti; Harianto, Feri (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2024)
Currently, the construction sector is adopting the theory of production in the manufacturing industry, known as lean construction, to reduce waste and increase value. Last Planner System (LPS) has not been widely used and has good potential because the advantage of LPS is to identify a job along with obstacles to improve performance in a construction project. In the construction of Junior High School (SMP) Al-Falah, it has work obstacles due to erratic weather so that the project is delayed, the author conducts a field survey to analyze the actual progress in the field, LPS has work indicators / work flow to measure the extent to which work indicators can be realized properly, the LPS work flow are Master Plan, Phase Pull Planning, Lookahead Planning, Constraints Analysis, Shielding Production, and Percent Plan Complete (PPC) as a standard for measuring whether project productivity is realized properly or not. In this study, the results of the implementation using LPS on the Al-Falah Junior High School construction project show that the lowest PPC can be seen in week 7, which is 0% because there is no work achievement so that the work is delayed, while in week 16 it can be seen that PPC has increased dramatically to 96%. Then after averaging the PPC of 51% which means that LPS has not been able to increase the reliability of planning above 70%, (Ballard, 2000).